Solve for X:
7x^2 + 14x + 12 = -8x^2 + 20
Responses

2, 16
2, 16 - no response given

4 3 , −25
4
3
,
−
2
5
4 3 , −25
4
3
,
−
2
5
- no response given

-2, -16

−43 , 25
3 answers
X = -2, -3
can you explain
Sure! To solve for X, we need to simplify the equation and then solve for X.
Given equation: 7x^2 + 14x + 12 = -8x^2 + 20
Combine like terms:
7x^2 + 14x + 12 + 8x^2 - 20 = 0
15x^2 + 14x - 8 = 0
Now, we can use the quadratic formula to solve for X, which is: x = (-b ± sqrt(b^2 - 4ac)) / 2a
In the equation 15x^2 + 14x - 8 = 0, a = 15, b = 14, c = -8
Substitute these values into the quadratic formula:
x = (-14 ± sqrt(14^2 - 4*15*(-8))) / 2*15
x = (-14 ± sqrt(196 + 480)) / 30
x = (-14 ± sqrt(676)) / 30
x = (-14 ± 26) / 30
Now we calculate both solutions:
x1 = (-14 + 26) / 30 = 12 / 30 = 0.4
x2 = (-14 - 26) / 30 = -40 / 30 = -1.33
Therefore, the solutions for X are X = -0.4, -1.33.
Given equation: 7x^2 + 14x + 12 = -8x^2 + 20
Combine like terms:
7x^2 + 14x + 12 + 8x^2 - 20 = 0
15x^2 + 14x - 8 = 0
Now, we can use the quadratic formula to solve for X, which is: x = (-b ± sqrt(b^2 - 4ac)) / 2a
In the equation 15x^2 + 14x - 8 = 0, a = 15, b = 14, c = -8
Substitute these values into the quadratic formula:
x = (-14 ± sqrt(14^2 - 4*15*(-8))) / 2*15
x = (-14 ± sqrt(196 + 480)) / 30
x = (-14 ± sqrt(676)) / 30
x = (-14 ± 26) / 30
Now we calculate both solutions:
x1 = (-14 + 26) / 30 = 12 / 30 = 0.4
x2 = (-14 - 26) / 30 = -40 / 30 = -1.33
Therefore, the solutions for X are X = -0.4, -1.33.